Clinical characteristics and prognosis of patients with very severe acute hypertension visiting the emergency department - Hyun-Jin Kim; Byung Sik Kim; Jeong-Hun Shin (BMC, 2022)
Abstract Background Data regarding very severe acute hypertension, a serious problem in emergency departments (EDs), are scarce. We investigated the clinical characteristics, practice patterns, and long-term prognoses of patients presenting to the ED with very severe acute hypertension. Methods Cross-sectional study data were obtained from a single regional emergency medical center, including patients aged ≥ 18 years who were admitted to the ED between January 2016 and December 2019 for very severe acute hypertension, which was defined as systolic blood pressure of > 220 mmHg and/or diastolic blood pressure of > 120 mmHg. The patients were classified into two groups based on the presence or absence of hypertension-mediated organ damage (HMOD). Results Among 1,391 patients with very severe acute hypertension in the ED, half of the them (50.2%) had a previous medical history of hypertension, and 547 (39.3%) had acute HMOD. The overall 3-month, 1-year, and 3-year mortality rates were 5.2%, 11.9%, and 17.3%, respectively. In particular, patients with HMOD had a significantly higher mortality rate at each time point than those without HMOD. Among patients with HMOD, acute ischemic stroke was the most common (28.7%). Moreover, intravenous antihypertensive drugs were significantly more prescribed in patients with HMOD than in those without HMOD (79.0% vs. 22.2%, P < 0.001), but there were no differences in oral antihypertensive drugs between the two groups. Conclusions Patients with very severe acute hypertension had poor long-term clinical prognoses. Clinicians should be continuously monitoring and providing appropriate treatment and close follow-up for patients with very severe acute hypertension.